Completing the public human resource management model based on job position in Vietnam - Nguyen Duc Quyen (Journal of State Management, 2024)
The public human resource management model based on job position, also known as the position-based civil service model, represents an approach to arranging personnel according to each specific task in an organization. Compared to the career-based model, implementing this model will increase the effectiveness and efficiency of human resource management activities in the public administration sector.